2018
DOI: 10.1002/mc.22829
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with SP1, but not binding to the E‐box motifs, is responsible for BHLHE40/DEC1‐induced transcriptional suppression of CLDN1 and cell invasion in MCF‐7 cells

Abstract: Basic helix-loop-helix family member e40 (BHLHE40) is located in 3p26.1 and acts as a transcriptional repressor of the circadian rhythm by suppressing the expression of the clock genes and clock-controlled genes. Recent research indicated that BHLHE40 may be involved in regulating tumor cell progression. However the mechanism by which BHLHE40 regulates the invasion and metastasis of tumor cells is unclear. Our in vitro assays showed that BHLHE40 promoted tumor cell invasion while BHLHE40 silencing by siRNA sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…BHLHE40 is expressed in a wide range of human tissues, and interacts with numerous nuclear proteins [31][32][33][34]. Apart from E-box binding, BHLHE40 was also shown to suppress transcription by binding to SP1 domains on target genes [35]. Targets of BHLHE40 regulated transcription are listed in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…BHLHE40 is expressed in a wide range of human tissues, and interacts with numerous nuclear proteins [31][32][33][34]. Apart from E-box binding, BHLHE40 was also shown to suppress transcription by binding to SP1 domains on target genes [35]. Targets of BHLHE40 regulated transcription are listed in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanisms are unclear. We previously reported that BHLHE40 regulates CLDN1 transcription and MCF‐7 cell invasion through binding with sp1 . In the current study, we aimed to explore whether BHLHE41 regulates cell invasion in the same manner as those found in the previous studies.…”
Section: Discussionmentioning
confidence: 66%
“…Members of this subfamily are involved in regulating various biological phenomena, such as circadian rhythm, cell proliferation, apoptosis, hypoxia and immune responses . A few recent studies have shown that BHLHE40 and BHLHE41 are involved in regulating cell invasion and metastasis . However, the underlying mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, DEC1 has been reported to promote tumor progression, invasion and metastasis (13)(14)(15)(16). Previous studies have shown that DEC1 is associated with various types of human cancers, such as lung, gastric, liver and breast cancer (17)(18)(19)(20). Recently, Zhou et al (21) found that knockdown of cryptochrome circadian regulator 1 enhanced the proliferation and migration of osteosarcoma cells presenting downregulation of DEC1.…”
Section: Introductionmentioning
confidence: 99%